APAKAH MANAJEMEN LABA TERKAIT DENGAN KEGIATAN PENGHINDARAN PAJAK? PERAN MODERASI KOMISARIS INDEPENDEN - Bisma Akbar Anggara Surya; Aditya Aditya; Amrie Firmansyah (JURNAL PAJAK INDONESIA, 2023)
This study examines the effect of earnings management on tax avoidance with an independent commissioner as a moderating variable in this relationship. The data this research uses comes from the financial reports of consumer goods companies listed on the Indonesia Stock Exchange from 2019 to 2021. Based on purposive sampling, this research sample consisted of 63 observations. Hypothesis testing was carried out utilizing multiple linear regression analysis for panel data. The test results show that earnings management does not affect tax avoidance. In addition, independent commissioners do not moderate the relationship between earnings management and tax avoidance. Based on the results of this test, the Tax Authorities in Indonesia need to identify factors of tax avoidance outside of earnings management activities.